Análise de estabilidade de taludes de aterro de resíduos urbanos utilizando parâmetros geotécnicos de propostas bibliográficas e correlações com Nspt - Remédio, Flávio Henrique [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The increase in waste generation rates, due to the increase of industrial activity and the population's purchasing power, compared to the scarcity of appropriate disposition of the waste areas, close to generating centers, has led managers to invest in increasing the capacity of load landfills in operation or reuse of old disposal areas closed to meet this demand. This leads to the construction of higher and higher landfill, reducing the problem of waste demand and, in turn, generating serious concerns over the stability of these bodies developed for studies in natural massive, with constitution and mechanical behavior of different materials disposed of in landfills. In this way, systematic studies have been performed in order to determine suitable geotechnical parameters waste present in Caetetuba Landfill, located at Atibaia/SP city. The geotechnical parameters of waste were determined based on proposals raised during the literature and based on survey results of penetration tests identified in documentary research. Several methods of slope stability analysis, raised during the literature search were evaluated to identify the most suitable method for applying the landfill Caetetuba of Health. To perform the stability analysis were prepared sections of the site, based on topographic maps and profiles polls identified in documentary research, which were implemented in SLOPE / W Geo-Slope International software. The findings were expressed in terms of security values, and compared the safety factors calculated by the various methods offered by the SLOPE / W software, depending on the variations in geotechnical parameters and analytical methods used. Within this context, the conventional slope stability calculation methods developed in soil mechanics are commonly used in the stability studies in landfills, by researchers and professionals. However, these work methodologies were

O aumento nas taxas de geração de resíduos, decorrentes do aumento das atividades industriais e do poder de compra da população, frente à escassez de áreas adequadas à disposição de resíduos, próximas aos centros geradores, tem levado as administradoras a investirem no aumento da capacidade de carga de aterros sanitários em operação ou na reutilização de antigas áreas de disposição encerradas, para suprir esta demanda. Esta situação induz a construção de aterros cada vez mais altos, atenuando o problema da demanda de resíduos e, em contrapartida, gerando grandes preocupações quanto à estabilidade destes corpos. Dentro deste contexto, os métodos convencionais de cálculo de estabilidade de taludes são comumente utilizados em estudos de estabilidade em aterros sanitários, por pesquisadores e profissionais especializados. No entanto, estas metodologias de trabalho foram desenvolvidas para estudos em maciços com constituição e comportamento mecânico distintos dos materiais dispostos em aterros sanitários. Desta forma, foram executados estudos sistemáticos com objetivo de determinar parâmetros geotécnicos adequados aos resíduos presentes no Aterro de Caetetuba, localizado no município de Atibaia - SP. Os parâmetros geotécnicos dos resíduos foram determinados com base em propostas levantadas durante a pesquisa bibliográfica e com base em resultados de testes de penetração de sondagens identificadas na pesquisa documental. Diversos métodos de análise de estabilidade de taludes, levantados durante a pesquisa bibliográfica, foram avaliados visando identificar o método mais adequado para aplicação no Aterro Sanitário de Caetetuba. Para realização das análises de estabilidade foram elaboradas seções litoconstrutivas do aterro, com base em plantas topográficas e perfis de sondagens identificados na pesquisa documental, as quais foram implementadas no software SLOPE/W da Geo-Slope International. As...
Keywords: Engineering geology; Geologia de engenharia; Aterro sanitário; Resíduos; Resíduos sólidos; Estabilidade; Atibaia (SP)